2001
DOI: 10.1029/2000jd900600
|View full text |Cite
|
Sign up to set email alerts
|

Measuring system for the long‐term monitoring of biosphere/atmosphere exchange of carbon dioxide

Abstract: Abstract.We

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 56 publications
1
48
0
Order By: Relevance
“…During this decade, two towers were also established in Europe, Hegyhatsal in Hungary for CO 2 (Haszpra et al, 2001) and Cabauw in the Netherlands for CO 2 and other trace gases (Vermeulen et al, 2006). From the Wisconsin tower, it has been shown that tall towers can have footprints extending over an area of approximately 10 6 km 2 (Gloor et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…During this decade, two towers were also established in Europe, Hegyhatsal in Hungary for CO 2 (Haszpra et al, 2001) and Cabauw in the Netherlands for CO 2 and other trace gases (Vermeulen et al, 2006). From the Wisconsin tower, it has been shown that tall towers can have footprints extending over an area of approximately 10 6 km 2 (Gloor et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The site can be considered as rural in the industrialized, densely populated Central Europe, as it was shown by SF 6 measurements (Haszpra et al, 2008). A detailed description of the site and instrumentation can be found in Haszpra et al (2001; or at the website of the station (http://nimbus.elte.hu/hhs/).…”
Section: Site Measurement Program and Instrumentationmentioning
confidence: 99%
“…The large-scale flow pattern at the station may only be influenced by the Alps some 100 km to the west. At Hegyhátsál tall tower site carbon dioxide dry mole fraction has been continuously monitored at four elevations (10 m, 48 m, 82 m and 115 m above the ground) since September 1994, using a nondispersive infrared gas analyzer (1994-2007: Li-Cor Model LI-6251, from 2007: Li-Cor Model LI-7000) (Haszpra et al, 2001;. Quality of the measurements is assured by use of standards produced and certified by the World Meteorological Organization Central Calibration Laboratory for CO 2 (WMO CCL) operated by the Earth System Research Laboratory of the National Oceanic and Atmospheric Administration (NOAA ESRL), USA, and by the comparison with co-located NOAA flask air sample measurements (NOAA co-operative air sampling network, site code: HUN -http://www.esrl.noaa.gov/gmd/ccgg/flask.html) (Haszpra et al, 2010), as well as through regular international intercomparisons (Manning et al, 2009).…”
Section: Site Measurement Program and Instrumentationmentioning
confidence: 99%
“…Measurements of CO 2 mixing ratio profiles, temperature, humidity, and wind profiles began in September 1994 (Haszpra et al 2001). Flux measurements began in April 1997.…”
Section: Monitoring Sitesmentioning
confidence: 99%
“…The system is designed for the continuous, unattended monitoring of CO 2 mixing ratio in the near surface atmosphere based on an infrared gas analyzer (IRGA) with a setup that is very similar to that described by Zhao et al (1997), and used for the measurements reported by Bakwin et al (1995Bakwin et al ( , 1998 and Haszpra et al (2001Haszpra et al ( , 2008 (Figure 2). At the station an ATOMKI type (described above) atmospheric CO 2 sampling unit was also installed.…”
Section: The Developed Field-deployable Co 2 Measuring Systemmentioning
confidence: 99%